Project management in state regulation: problems and solutions (Journal of Economic Research & Business Administration, 2019)
Increased globalization has led to the widespread application of project management systemsin many areas of business operations. This article is intended to examine the theoretical and methodologicalapproaches to project management in ensuring the competitiveness of the national economyas it pertains to the implementation of its government programs and projects. Through the scientificanalysis of current-day publications on project management in the public sector, the authors substantiatethe need for its introduction into Kazakhstan’s practice, which will increase the competitiveness ofeconomic activity. The theoretical and methodological substantiation is based on the utilization of themagic triangle of project management: “quality – time – budget”, which makes it possible to developalgorithms for the performance of the main functions of project management by government agencies.The article emphasizes the need to use the international experience in the practical implementationof project management of public authorities in the execution of government programs and projects in the context of global instability, accompanied by various risks, crisis situations, limited resources, and manyother effects. In the national science, there is yet a lot to be done on a thorough analysis of a projectmanagement system implementation in government agencies on the path of Kazakhstan’s entry into thetop 30 most competitive countries in the world.In this regard, this article discusses issues arising in the implementation of the project managementsystem in the government bodies of the Republic of Kazakhstan and ways to address them.